Democratic tension in the election of judges in Mexico - Chávez Cervantes, José de Jesús (DIXI, 2024)
The democratic tension of modern constitutionalism represents a problem that can hardly find intermediate points. Thus, the recent constitutional reform of the judiciary in Mexico is an excellent test laboratory to study the viability of the election of judges. The purpose of this article is to describe positions that encourage the election of judges within the framework of the constitutional State and the tension that arises in the face of a Constitution of rights. Likewise, reference will be made to the context of the Mexican State, and risks and possible consequences will be noted in relation to the very democratic legitimacy that is so much in dispute. In any case, if we want to continue deciding in democracy, we must take into account —or at least address in a broader and more detailed way— what we discuss and decide, thinking that, in order to continue deciding, we will have to put dikes to democracy itself.
Keywords: Constitution; popular judges; democracy; legitimacy